Preparation and characterization of PVA/PASA-PVA/PDDAB bipolar membrane - Espinoza-Gómez,Heriberto (2009)
Bipolar membranes (BMP) were prepared by bonding together separate anion and cation exchange membrane. For the preparation of the cation selective layer, aqueous solution of PVA [poly(vinyl alcohol)], and PASA [poly(anetholesulfonic acid sodium salt)], where the ratio of PVA/PASA was changed for the control of the membrane charge density, were cast for negatively charged membranes. These membranes were annealed at 100 ºC for 45 min and cross-linked in an aqueous solution containing 10% Na2SO4, 1.5% H2SO4, and 0.5% glutaraldehyde in order to control water content of the gel membranes. The anion selective layers were prepared by dispersing a solution of PVA and PDDAB [poly(diallyldiethylammonium bromide)] in DMF, where the ratio of PVA/PDDAB was changed for the membrane charge density control. The electrical resistance of BMP formed by this methodology was slightly increased while the selectivity decreased, while their permselectivity did not change with the acid or alkaline post-treatment.